Pengaruh latihan imagery terhadap latihan shooting pada Atlet Petanque Kabupaten Bekasi - Wijaya, Angga; Iskandar, Tatang; Rasyono, Rasyono (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2023)
This research is motivated by the inconsistency of the athlete's shooting ability due to the lack of athlete's confidence during the match. This study aims to determine the effect of imagery training on shooting results at Petanque Athletes in Bekasi. The method used in this study was an experiment with a